THEORETICAL ASPECTS (DEFECTS) OF THE PREVENTION DIRECTION IN MEDICINE (CARDIOLOGY) AND THEIR APPLIED SIGNIFICANCE: CRITICS AND SUGGESTIONS - A. S. Dimov (Кардиоваскулярная терапия и профилактика)
Prevention of the diseases, particularly cardial pathology, has its very significant controversies. The idea of the risk factors did not give the expected results. Causality of the majority of diseases is still unknown or not fully understood. This leads to inability of predicting. The article provides the reader with theoretical and practical experience evaluation of the XX century upon the problem of causality (etiology) of diseases. The original definition of causality is expressed and vindicated as its applied significance.